The effect of high-intensity gamma radiation on PETG and ASA polymer-based fused deposition modelled 3D printed parts - SAM CRESSALL (Journal of Materials Science, 2024)
There is growing interest in the application of 3D printing for demanding environments subject to gamma radiation in areas such as the nuclear industry and space exploration. In this work, the effect of gamma radiation on fused deposition modelled 3D printed parts composed of polyethylene terephthalate glycol (PETG) and acrylic styrene acrylonitrile (ASA) polymers was studied. Dose levels of up to 2.25 MGy were applied to the printed components, doses equivalent to over 1 year operating near spent nuclear fuel cells. Infrared spectroscopy showed the evidence of cross-linking by the formation of peaks corresponding to –OH and C–H bonds. Tensile and hardness testing was used to assess changes in mechanical properties and showed a reduction in ultimate tensile stress and maximum strain in parts made from both polymers, but with PETG retaining greater strength and ductility than ASA, especially at intermediate gamma exposure. Young’s modulus and hardness showed either modest increases or a fairly flat response with exposure. Mechanical properties were heavily dependent on the build structure, with horizontal build samples pulled parallel to the filament direction being several times stronger than vertical build samples pulled normal to the layers. Non-irradiated samples pulled parallel to the filament direction were indicative of ductile failure, with rough surfaces, distinct infill and wall regions and evidence of thinning occurring after fracture, but irradiated fracture surfaces were flatter, smoother and without local thinning, suggesting gamma radiation-induced embrittlement in the material. For samples pulled perpendicular to the filament direction, all fractures occurred between layers, creating flat fracture surfaces with no evidence of necking and indicative of brittle failure regardless of whether the samples were irradiated.